Identification of several novel Neurospora genes in the lambda-ZAP I and lambda-ZAP II libraries - Roxanne A. Yamashita; W. Dorsey Stuart (Fungal Genetics Reports, 1996)
Polyclonal antibodies to and oligonucleotides derived from N-terminal sequences of media proteins of Neurospora crassa were both used to screen the FGSC lambda-ZAP I and lambda-ZAP II cDNA libraries. Primary sequencing of the identified phagemids revealed homologies to a number of known genes. These genes are listed and the cDNA clones are available from our laboratory to interested parties.